Academic e-books : publishers, librarians, and users - Ward, Suzanne M.; Freeman, Robert S.; Nixon, Judith M. (West Lafayette, Indiana : Purdue University Press, 2016)
"Academic E-Books: Publishers, Librarians, and Users provides reader s with a view of the changing and emerging roles of electronic books in higher education. The three main sections contain contributions by exp erts in the publisher/vendor arena, as well as by librarians who report on both the challenges of offering and managing e-books and on the iss ues surrounding patron use of e-books. The case study section offers pe rspectives from seven different sizes and types of libraries whose libr arians describe innovative and thought-provoking projects involving e-b ooks. Read about perspectives on e-books from organizations as diverse as a commercial publisher and an association press. Learn about the vie wpoint of a jobber. Find out about the e-book challenges facing librari ans, such as the quest to control costs in the patron-driven acquisitio ns (PDA) model, how to solve the dilemma of resource sharing with e-boo ks, and how to manage PDA in the consortial environment. See what patro n use of e-books reveals about reading habits and disciplinary differen ces. Finally, in the case study section, discover how to promote schola rly e-books, how to manage an e-reader checkout program, and how one li brary replaced most of its print collection with e-books. These and oth er examples illustrate how innovative librarians use e-books to enhance users' experiences with scholarly works"--
Publishers' and vendors' products and services -- An industry perspe ctive: publishing in the digital age / Nadine Vassallo -- The journey b eyond print: perspectives of a commercial publisher in the academic mar ket / Rhonda Herman -- The university press perspective on e-books in l ibraries: production, marketing, and legal challenges / Tony Sanfilippo -- Delivering American Society for Microbiology e-books to libraries / Christine B Charlip -- Platform diving: a day in the life of an academ ic e-book aggregator / Bob Nardini -- Librarians' challenges -- Univer sity of California, Merced: primarily an electronic library / Jim Doole y -- Patron-driven acquisitions: assessing and sustaining a long-term P DA e-book program / Karen S. Fischer -- Use and cost analysis of e-book s: patron-driven acquisitions plan vs librarian-selected titles / Suzan ne M. Ward & Rebecca A. Richardson -- E-books across the consortium: re flections and lessons from a three-year DDA experiment at the Orbis Cas cade Alliance / Kathleen Carlisle Fountain -- The simplest explanation: Occam's reader and the future of interlibrary loan and e-books / Ryan Litsey, Kenny Ketner, Joni Blake, & Anne McKee -- Developing a global e -book collection: an exploratory study / Dracine Hodges -- Users' exper iences -- A social scientist uses e-books for research and in the class room / Ann-Marie Clark -- The user experience of e-books in academic li braries: perception, discovery and use / Tao Zhang & Xi Niu -- E-book r eading practices in different subject areas: an exploratory log analysi s / Robert S. Freeman & E. Stewart Saunders -- Library e-book platforms are broken: let's fix them / Joelle Thomas & Galadriel Chilton -- Case studies -- A balancing act: promoting Canadian scholarly e-books while controlling user access / Ravit H. David -- Of Euripides and e-books: the digital future and our hybrid present / Lidia Uziel, Laureen Esser, & Matthew Connor Sullivan -- Transitioning to e-books at a medium-size d academic library: challenges and opportunities: a feasibility study o n psychology collection / Aiping Chen-Gaffey -- E-books and a distance education program: a library's failure rate in supplying course reading s for one program / Judith M. Nixon -- Mobile access to academic e-book content: a Ryerson investigation / Naomi Eichenlaub & Josephine Choi - - E-reader checkout program / Vincci Kwong & Susan Thomas -- Out with t he print and in with the e-book: a case study in mass replacement of a print collection / Stephen Maher & Neil Romanosky -- Epilogue / Michael Levine-Clark -- Contributors.
Includes bibliographical references and index.
Keywords: Libraries -- Special collections -- Electronic books; Academic libraries -- Collection development; Scholarly electronic publishing; Libraries and electronic publishing; Academic libraries -- United States -- Case studies